Information Communication Technology and Student Personnel Services in Osun State Higher Learning Institutions - Fashiku Christopher Oluwatoyin; Adewumi Olusegun Daniel; Ayoku Oba Baba (Universitas Pendidikan Indonesia (UPI), 2023)
The study was conducted to investigate the existing information communication technology (ICT) facilities and students’ personnel services in Osun State Colleges of Education and Polytechnics. The descriptive survey design was used in the study. The population for the study consisted of academic staff, non-teaching staff, and students of Osun State Colleges of Education and Polytechnics. The sample comprised 376 respondents which included 97 academic staff, 112 non-teaching staff, and 167 students in Osun State Colleges of Education and Polytechnics using a multi-stage sampling technique. Two sets of research instruments were used to collect data for the study, A self-designed questionnaire titled Information Communication Technology and Students’ Personnel Services Questionnaire (ICTSPSQ) was used to collect information from the respondents, and an Observation Checklist titled Information Communication Technology Facilities (ICTF) to collect additional information in the study. The reliability index of the questionnaire was 0.74. The result indicated that ICT enhanced students’ personnel services in the institutions while there was a significant difference in ICT usage and students’ personnel services in Osun State Colleges of Education (F=4.47; p 0.005) and Polytechnics (F=4.61; p 0.005) respectively. It was recommended that Colleges of Education should put more effort into making sure that those personnel services provided for students are more digitalized for efficiency and effectiveness.